A retrospective analysis of Enterobius vermicularis frequency for the last five years in Aydin, Turkey (Annals of Medical Research, 2021)
Aim: Enterobius vermicularis (pinworm) is a parasitic nematode that infects humans and causes gastrointestinal symptoms mostly in children. This retrospective study aimed to analyze cellophane tape (CT) examination findings from a parasitology laboratory in Aydin, Turkey.Materials and Methods: The present study included the CT examination results in Aydin Adnan Menderes University, Faculty of Medicine, Parasitology Laboratory from January 2016 to October 2020. Perianal CT preparations were screened for the presence of pinworm eggs with direct microscopy. Changes in the frequency of E. vermicularis by years and according to gender were evaluated. Statistical analyses were performed with Pierson Chi-square test.Results: Pinworm eggs were detected in 436 (8.2%) of 5300 perianal CT preparations during the study period of time. There was a decrease in the frequency of parasite in the last two years (p
Keywords: Aydin; Enterobius vermicularis; frequency; gender